Cloning, expression and purification of m-cell specific binding peptide (CO1) fused with GFP - An, Nguyen Hoang; Truong, Dang Tat; Hieu, Tran Van (Vietnam Journal of Biotechnology, 2018)
Despite many advantages over injection vaccines such as cost effectiveness, safety and easy to use, and so on, oral vaccines are negligibly concerned. This is mostly because of the availability of vast surface in the gastro-intestinal tract, thereby requiring lot of antigens which could hamper their potential. To circumvent this issue, a novel strategy for targeting antigens to M cells (microfold cells), a minority of cells located in the small intestine for antigen transportation, is utilized by making a fusion protein comprised of an antigen with an M cell specific ligand. Discovered via biopanning, Co1 peptide is a potential ligand because of its small size (12 amino acids) and having an adjuvant capacity. To develop a monitoring model, we fused GFP (green fluorescent protein) as a monitoring marker with Co1 peptide. Initially, co1-gfp fusion gene was created by overlap extension PCR on GFP-encoded vector backbone, then it was incorporated into an expression vector pET22b before transforming into E. coli DH5α. The recombinant vector was screened by PCR method, sequenced and aligned with designed sequences. The in-frame vector was then introduced into E. coli BL21(DE3) for expression by inducing with 0.5mM IPTG. Fusion protein was purified using Ni-affinity chromatography. The results showed that the fused genes were in-frame cloned and completely matched with the designed sequences. SDS-PAGE and Western blot analyses showed Co1-GFP protein expressed in soluble form and could be purified at one-step elution of 500mM imidazole. The purified fusion protein could emit fluorescent light under UV excitation. Collectively, recombinant Co1-GFP fusion protein was successfully produced and its potential applications need to be warranted.